High crystallinity polyether ketone ketone and preparation method and application thereof

CN122940984APending Publication Date: 2026-10-20SUZHOU PAIKE TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410604098.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-15
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0009]CN109593183A公开了一种采用无规共聚在聚合物主链上引入一种能够成核的分子结构,使其在成型加工过程中可以快速的形成结晶核,进一步促进结晶速度的提高,同时促进结晶度的提高,所制备的聚醚酮酮材料在成型加工过程中可以有效的降低成本,但是该方案改变了聚醚酮酮原有主链结构,只是简单说明提高结晶度,但未对材料的机械性能和耐热性说明

Benefits of technology

[0073]本发明提供的高结晶度聚醚酮酮的制备方法采用嵌段共聚的方式,分两次加入含两个活性酰氯的芳香单体进行反应,在未外加任何助剂的情况下,使制备得到的聚醚酮酮具有较高的结晶度以及较快的结晶速率,还具有邻位键结构异构体含量较低的特点,同时整体制备过程操作十分简单,大大提高了材料性能,降低成型加工的生产时间,有效解决了现存聚醚酮酮产品结晶度较低、生产效率不高以及熔融不稳定的问题,非常适合工业化生产使用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004841464450000051
    Figure BDA0004841464450000051
  • Figure BDA0004841464450000152
    Figure BDA0004841464450000152
  • Figure FDA0004841464440000021
    Figure FDA0004841464440000021
Patent Text Reader

Abstract

This invention provides a high-crystallinity polyether ketone ketone, its preparation method, and its applications. The preparation method employs block copolymerization, adding an aromatic monomer containing two active acyl chlorides in two separate reactions. Without the addition of any external additives, the prepared polyether ketone ketone exhibits high crystallinity and a fast crystallization rate, as well as a low content of ortho-bonded isomers, significantly improving the material's mechanical properties and thermal stability. Furthermore, the overall preparation process is very simple, reducing molding and processing time. This effectively solves the problems of low crystallinity, low production efficiency, and unstable melting in existing polyether ketone ketone products, making it highly suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer synthesis technology, specifically relating to a highly crystalline polyether ketone ketone, its preparation method, and its applications. Background Technology

[0002] Among thermoplastic resins, polyaryletherketones (PAEKs), such as polyetheretherketone (PEEK) and polyetherketoneketone (PEKK), possess excellent heat resistance, chemical resistance, and mechanical strength, making them highly sought after in the aerospace field. PEKK, in particular, allows for the modification of its properties by altering the ratio of terephthaloyl (T) to isophthaloyl (I) moieties within its structure, enabling tailoring to the specific properties and molding conditions required for various components.

[0003] The arrangement of repeating units in the PEKK chain affects the crystallization rate and crystallinity of the polymer. Higher chemical and stereoregularity of the chain leads to a faster crystallization rate and higher crystallinity. The polymer may crystallize in discrete regions of structural units A and B, or in a disordered manner, or somewhere in between. This has a decisive impact on the macroscopic properties of the polymer, namely mechanical properties (such as stiffness and toughness), fracture resistance, and even chemical resistance. Theoretically, para-linked polymers exhibit higher crystallinity than their ortho, meta, or mixed isomers within the same polymer family, thus possessing higher mechanical properties, fracture resistance, and even chemical resistance.

[0004] A:

[0005] B:

[0006] Especially for PEKK composites, at 180℃, the mechanical properties of PEKK composites with lower crystallinity are significantly reduced compared to those with higher crystallinity, with Young's modulus and shear modulus decreasing by about 90%. At room temperature, the Young's modulus and shear modulus of incompletely crystalline or even amorphous PEKK composites are reduced by 11% and 28% respectively compared to fully crystalline PEKK composites, indicating that crystallinity has a significant impact on the performance of composites.

[0007] Currently, PEKK is industrially prepared by the Friedel-Crafts catalytic condensation of diphenyl ether, terephthaloyl chloride, and isophthaloyl chloride in an inert solvent (e.g., o-dichlorobenzene, nitromethane, or dichloroethane). The most commonly used catalyst is aluminum chloride. PEKK produced by this method typically has xanthonesol end groups resulting from the ortho-acylation of diphenyl ether. These xanthonesols are highly unstable and easily decompose upon heating, releasing xanthonesol and forming phenyl radicals. These phenyl radicals react with the polymer, causing cross-linking and degradation through hydrogen abstraction, thus severely impacting the material's mechanical properties. Furthermore, due to the influence of the isophthaloyl moiety, it exhibits a tendency towards low crystallization rates. Therefore, the Friedel-Crafts catalytic method not only suffers from increased molding time but also presents problems during processing.

[0008] To address the aforementioned issues, current research has disclosed copolymers of diphenyl ether, isophthaloyl halides, and isophthaloyl halides. However, these only describe random copolymers, i.e., copolymers in which isophthaloyl and isophthaloyl units are randomly dispersed along the polymer backbone. Furthermore, due to various reasons, the utility of these random coetherketones is limited, and their upper limit of operating temperature is too low. In addition, at lower T / I ratios, the coetherketones decrease in size and become more sensitive to solvent and stress cracking. Finally, random coetherketones exhibit poor crystallinity. This necessitates holding them for a longer period during molding to achieve the desired level of crystallinity.

[0009] CN109593183A discloses a method that introduces a nucleating molecular structure into the polymer backbone using random copolymerization, enabling rapid formation of crystal nuclei during molding and processing, thereby further promoting the increase in crystallization speed and crystallinity. The prepared polyether ketone ketone material can effectively reduce costs during molding and processing. However, this method alters the original backbone structure of polyether ketone ketone and only briefly mentions improving crystallinity, without describing the mechanical properties and heat resistance of the material.

[0010] CN107973902A discloses a method for preparing block polyether ketone ketone. A solvent, Lewis acid, and Lewis base are added to two prepolymer reaction flasks, respectively. Then, diphenyl ether and m- / terephthaloyl chloride in equimolar ratios are added and reacted to generate prepolymers A and B with good flowability. Prepolymers A and B are then added to a polymerization reaction flask for further reaction. After crushing, washing, and drying, block polyether ketone ketone is prepared. This invention has a simple process and low cost, and the prepared polyether ketone ketone has high crystallinity and a fast crystallization rate. However, this method has a complex reaction process, many side reactions, difficulty in controlling molecular weight, and the possibility of cyclization.

[0011] Therefore, there is still a need in the field to develop a preparation method for polyetherketoneketone that can improve the crystallinity and crystallization rate of polyetherketoneketone without relying on any external additives while maintaining absolute purity. Summary of the Invention

[0012] To address the shortcomings of existing technologies, the present invention aims to provide a high-crystallinity polyether ketone ketone, its preparation method, and its applications. The preparation method is very simple and can produce polyether ketone ketone with high crystallinity and fast crystallization rate without the addition of any additives. It also has the characteristic of low content of structural isomers of ortho-position bonds, which greatly improves the mechanical properties and thermal stability of the material, reduces the production time of material molding and processing, and improves production efficiency.

[0013] To achieve this objective, the present invention employs the following technical solution:

[0014] In a first aspect, the present invention provides a method for preparing highly crystalline polyether ketone, the method comprising the following steps:

[0015] (1) Mix an aromatic monomer containing two active hydrogens, an aromatic monomer containing two active acyl chlorides and a solvent, cool down for the first time, then add a first acid catalyst, heat up for the first time and carry out the first reaction, then add the isomer of the aromatic monomer containing two active acyl chlorides, a second acid catalyst and a capping agent, heat up for the second time and carry out the second reaction to obtain the reaction product.

[0016] (2) The reaction product obtained in step (1) is subjected to decomplexation and post-treatment to obtain the highly crystalline polyether ketone ketone.

[0017] The method for preparing highly crystalline polyether ketone ketone provided by this invention involves a two-step reaction. First, an aromatic monomer containing two active hydrogens, an aromatic monomer containing two active acyl chlorides, and a capping agent are reacted. Then, an isomer of the aromatic monomer containing two active acyl chlorides is added to the reaction. The block copolymerization method described above helps to avoid the generation of side reactions, thereby resulting in a lower content of structural isomers with ortho-position bonds in the prepared polyether ketone ketone. Compared with random copolymer polyether ketone ketone with the same composition ratio, it has better mechanical properties and solvent stress cracking resistance at high temperatures and can be rapidly molded.

[0018] Meanwhile, the preparation method provided by the present invention has a very simple overall preparation process, and can produce polyether ketone ketone with high crystallinity and fast crystallization rate without the addition of any external additives, which effectively reduces the production time of molding and processing and improves production efficiency.

[0019] Furthermore, the highly crystalline polyether ketone ketone prepared by the preparation method provided by this invention can be processed into products for use. For example, it can be prepared from the molten phase by means of extrusion molding, injection molding, compression molding, 3D printing, or laser sintering. The products prepared include, but are not limited to, films, filaments, mechanical parts, etc. It can also be coated on substrates in the form of coatings using conventional coating techniques. Specific substrates include, but are not limited to, metal wires, films, fabrics, etc., and its applications are very wide.

[0020] It should be noted that the "high crystallinity polyether ketone ketone" in the present invention refers to polyether ketone ketone with a crystallinity of not less than 3.8%.

[0021] In fact, for the preparation method provided by this invention, there are no special restrictions on the specific types of aromatic monomers containing two active hydrogens, aromatic monomers containing two active acyl chlorides, and their isomers, as long as they contain two active hydrogens or two active acyl chlorides. However, in order to obtain the highest crystallinity and optimal mechanical properties of the high-crystallinity polyether ketone ketone, the following preferred options are made:

[0022] Preferably, the aromatic monomer containing two active hydrogens in step (1) includes any one or a combination of at least two of bis(phenoxybenzoyl) ketone, 1,4-bis(4-phenoxybenzoyl)benzene or 1,3-bis(4-phenoxybenzoyl)benzene, and more preferably 1,4-bis(4-phenoxybenzoyl)benzene and / or 1,3-bis(4-phenoxybenzoyl)benzene.

[0023] Preferably, the aromatic monomer containing two active acyl chlorides in step (1) is an aromatic monomer with a para structure, and the isomer of the aromatic monomer containing two active acyl chlorides is an aromatic monomer with a meta structure.

[0024] Preferably, the aromatic monomer containing two active acyl chlorides in step (1) is an aromatic monomer with a meta structure, and the isomer of the aromatic monomer containing two active acyl chlorides is an aromatic monomer with a para structure.

[0025] Preferably, the aromatic monomer having a para structure includes any one or a combination of at least two of the following compounds B1 to B5;

[0026]

[0027] Preferably, the aromatic monomer having a para-position structure is terephthaloyl chloride.

[0028] Preferably, the aromatic monomer having a meta structure is a meta isomer of the above compounds B1 to B5.

[0029] Preferably, the aromatic monomer having a meta-structure is isophthaloyl chloride.

[0030] Preferably, the capping agent in step (1) includes any one or a combination of at least two of benzoyl chloride, 4-phenoxybenzophenone, benzenesulfonyl chloride, 4-biphenyl, bis(4-oxyphenyl) ketone or biphenyl.

[0031] Preferably, based on the total molar amount of the aromatic monomer containing two active hydrogens, the aromatic monomer containing two active acyl chlorides and its isomers and the capping agent in step (1) being 100%, the molar content of the aromatic monomer containing two active hydrogens in step (1) is 48-51%, for example 48%, 48.5%, 49%, 49.5%, 50%, 50.5% or 51%, etc.

[0032] Preferably, based on the total molar amount of the aromatic monomer containing two active hydrogens, the aromatic monomer containing two active acyl chlorides and its isomers and the capping agent in step (1) being 100%, the molar content of the aromatic monomer containing two active acyl chlorides in step (1) is 25% to 50%, for example, 25%, 30%, 35%, 40%, 45% or 50%.

[0033] Preferably, based on the total molar amount of the aromatic monomer containing two active hydrogens, the aromatic monomer containing two active acyl chlorides and its isomers and the capping agent in step (1) being 100%, the molar content of the isomers of the aromatic monomer containing two active acyl chlorides in step (1) is 5% to 25%, for example, 5%, 10%, 15%, 20% or 25%.

[0034] Preferably, based on the total molar amount of the aromatic monomer containing two active hydrogens, the aromatic monomer containing two active acyl chlorides and its isomers and the capping agent in step (1) being 100%, the molar content of the capping agent in step (1) is 1 to 11%, for example, 1%, 2%, 4%, 6%, 8%, 10% or 11%.

[0035] It should be noted that the addition of the end-capping agent can terminate the continuous growth of at least one end of the polymer chain segment, thereby controlling the molecular weight of the obtained polymer; in addition, the amount of the end-capping agent or a certain monomer may be excessive, resulting in an imbalance in the ratio (the ratio is balanced when the stoichiometry of the active acyl chloride monomer and the active hydrogen monomer is 1:1), thereby controlling the molecular weight of the obtained target polyether ketone ketone and obtaining polyether ketone ketones with different molecular weights.

[0036] Preferably, in step (1), both the first acid catalyst and the second acid catalyst are Lewis acid catalysts.

[0037] Preferably, the Lewis acid catalyst comprises any one or a combination of at least two of the following: anhydrous aluminum chloride, zinc chloride, aluminum tribromide, antimony pentachloride, antimony pentafluoride, indium chloride, boron chloride, boron fluoride, ferric chloride, tin chloride, titanium tetrachloride, or molybdenum pentachloride.

[0038] Preferably, with the total molar amount of carbonyl groups in the system of step (1) being 100%, the total molar amount of the first acid catalyst and the second acid catalyst in step (1) is 100% to 300%, for example, 100%, 120%, 140%, 160%, 180%, 200%, 220%, 240%, 260%, 280%, or 300%, etc., more preferably 110% to 250%, even more preferably 120% to 220%, even more preferably 130% to 200%, and most preferably 140% to 180%.

[0039] Preferably, the solvent in step (1) includes any one of dichloromethane, 1,2-dichloroethane, o-dichlorobenzene, tetrachloroethylene, 1,2,4-trichlorobenzene, o-difluorobenzene, nitromethane, nitrobenzene, 1,3-dichlorobenzene, or 1,1,2,2-tetrachloroethane, more preferably o-dichlorobenzene and / or dichloromethane, and even more preferably o-dichlorobenzene; it is clear that the reaction temperature in step (1) cannot exceed the boiling point of the solvent, otherwise it will affect the morphology and properties of the final polymer.

[0040] Preferably, the molar concentration of the aromatic monomer containing two active hydrogens in the system of step (1) is 0.05 to 0.5 mol / L, for example, 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L or 0.5 mol / L.

[0041] Preferably, the mixing in step (1) is carried out in a polymerization reactor, which may be a stainless steel reactor, an enamel reactor, or a glass reactor, etc.

[0042] Preferably, the temperature of the system after the first cooling in step (1) is -30 to -5℃, for example -30℃, -25℃, -20℃, -15℃, -10℃ or -5℃.

[0043] Preferably, the temperature of the system after the first heating in step (1) is 0 to 150°C, for example, 0°C, 10°C, 20°C, 40°C, 60°C, 80°C, 100°C, 120°C, 140°C or 150°C.

[0044] Preferably, the time for the first reaction in step (1) is 0.1 to 12 hours, such as 0.1 hours, 1 hour, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours or 12 hours, and more preferably 4 to 8 hours.

[0045] Preferably, step (2) includes a second cooling step before adding the isomer of the aromatic monomer containing two active acyl chlorides, the second acid catalyst, and the capping agent.

[0046] Preferably, the temperature of the system after the second cooling is -30 to 50°C, for example -30°C, -20°C, -10°C, 0°C, 10°C, 20°C, 30°C, 40°C, or 50°C.

[0047] Preferably, the temperature of the system after the second heating in step (1) is 50 to 150°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.

[0048] Preferably, the time for the second reaction in step (1) is 0.1 to 12 hours, such as 0.1 hours, 1 hour, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours or 12 hours, and more preferably 4 to 8 hours.

[0049] Preferably, both the first and second reactions in step (1) are carried out under protective gas conditions.

[0050] Preferably, the protective gas includes nitrogen, argon, or helium.

[0051] Preferably, the method for decomplexing in step (2) includes: transferring the reaction product obtained in step (1) to a decomplexing vessel and adding a proton solution for decomplexing.

[0052] Preferably, the proton solution comprises any one or a combination of at least two of the following: water, dilute hydrochloric acid aqueous solution, dilute hydrochloric acid methanol solution, methanol, ethanol, acetone, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl ether, diethyl ether, tetrahydrofuran, trimethylamine, trimethylamine hydrochloride, dimethyl sulfide, tetramethylene sulfone, benzophenone, tetramethylammonium chloride, or isopropanol. More preferably, it comprises ice water, cooled dilute hydrochloric acid aqueous solution, or dilute hydrochloric acid methanol solution.

[0053] Preferably, the amount of proton solution added is greater than the total amount of the first acid catalyst and the second acid catalyst in step (1).

[0054] Preferably, the post-processing in step (2) includes centrifugation, washing and drying.

[0055] Preferably, the cleaning reagent includes one or a combination of at least two of the following: water, methanol, ethanol, acetone, dichloromethane, 1,2-dichloroethane, o-dichlorobenzene, N,N-dimethylformamide, N,N-dimethylacetamide, or N-methylpyrrolidone.

[0056] In a second aspect, the present invention provides a highly crystalline polyether ketone ketone, which is prepared by the preparation method described in the first aspect.

[0057] The highly crystalline polyether ketone obtained in the second aspect of this invention has two repeating units, A and B, as follows:

[0058] A:

[0059] B:

[0060] Preferably, the highly crystalline polyether ketone ketone has the morphology of a porous, irregular fine-grained solid, spherical particles, or powder.

[0061] Preferably, the intrinsic viscosity of the highly crystalline polyether ketone is 0.5 to 2.5 dL / g, such as 0.5 dL / g, 1 dL / g, 1.5 dL / g, 2 dL / g, or 2.5 dL / g, more preferably 0.6 to 2.0 dL / g, even more preferably 0.7 to 1.8 dL / g, and even more preferably 0.8 to 1.3 dL / g.

[0062] Preferably, the crystallinity of the high-crystallinity polyether ketone ketone is ≥3.8%, such as 3.8%, 7.6%, 11.5%, 15.4%, 23.1%, 30.7%, 34.6%, or 38.5%, etc. It should be understood that the crystallinity of the high-crystallinity polyether ketone ketone ≥3.8% does not refer to the crystallinity of a single polyether ketone ketone component, but rather to the crystallinity of different series of polyether ketone ketone products. Different series of polyether ketone ketone products have different ratios of A and B in the polyether ketone ketone structural unit, for example, A:B is 100:0, 90:10, 80:20, 70:30, 60:40, 50:50, etc.

[0063] Preferably, the enthalpy of melting of the highly crystalline polyether ether ketone is >5 J / g, for example, 5 J / g, 10 J / g, 15 J / g, 20 J / g, 25 J / g, 30 J / g, 35 J / g, 40 J / g, 45 J / g or 50 J / g, more preferably ≥20 J / g, even more preferably ≥30 J / g, and still more preferably ≥41 J / g; the above enthalpy of melting is measured with reference to standard ISO11357-3:2018, during the second heating and using a heating rate of 10℃ / min.

[0064] Thirdly, the present invention provides the application of highly crystalline polyether ketone as described in the second aspect in the preparation of composite materials.

[0065] Fourthly, the present invention provides a polyether ketone ketone composite material, the polyether ketone ketone composite material comprising reinforcing fibers and highly crystalline polyether ketone ketone as described in the second aspect.

[0066] The highly crystalline polyether ketone ketone provided in the second aspect of the present invention can be used as a substrate for reinforcing fibers in composite materials, and there are no particular limitations on the reinforcing fibers. However, in order to obtain composite materials with higher overall performance, the following reinforcing fibers are preferred:

[0067] Preferably, the reinforcing fiber includes any one or a combination of at least two of carbon fiber, glass fiber, aramid fiber, silicon carbide fiber, polyester fiber, ceramic fiber, alumina fiber, boron fiber, metal fiber, mineral fiber, rock fiber, or slag fiber. More preferably, it is a combination of any one or at least two of carbon fiber, glass fiber, or aramid fiber. Even more preferably, it is carbon fiber, which has superior specific strength and specific modulus of elasticity. Preferably using it as the reinforcing fiber of the composite material can give the obtained polyether ketone ketone composite material the advantages of lightweight and high strength.

[0068] Preferably, the polyetherketone-ketone composite material also contains fillers and / or additives.

[0069] Preferably, the filler comprises any one or a combination of at least two of talc, mica, kaolin, calcium carbonate, calcium silicate, or boron nitride.

[0070] Preferably, the filler also includes conductive particles.

[0071] Preferably, the additives include any one or a combination of at least two of antioxidants, light stabilizers, flame retardants, plasticizers, inorganic fillers, or internal mold release agents.

[0072] Compared with the prior art, the present invention has the following beneficial effects:

[0073] The high-crystallinity polyether ketone ketone provided by this invention adopts a block copolymerization approach, adding an aromatic monomer containing two active acyl chlorides in two separate reactions. Without adding any external additives, the prepared polyether ketone ketone exhibits high crystallinity and a fast crystallization rate, as well as a low content of ortho-bonded structural isomers. Furthermore, the overall preparation process is very simple, greatly improving material properties, reducing molding and processing time, and effectively solving the problems of low crystallinity, low production efficiency, and unstable melting in existing polyether ketone ketone products. It is highly suitable for industrial production. Attached Figure Description

[0074] Figure 1 The 1H NMR spectrum of the highly crystalline polyether ketone prepared in Example 1;

[0075] Figure 2 The DSC curve of the highly crystalline polyether ketone prepared in Example 1 is shown below.

[0076] Figure 3 The TGA thermogravimetric curve of the highly crystalline polyether ketone prepared in Example 1 is shown. Detailed Implementation

[0077] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0078] Example 1

[0079] A method for preparing highly crystalline polyether ketone includes the following steps:

[0080] (1) Nitrogen gas was introduced into a dry 2L reactor. 48g (0.1mol) of 1,4-bis(phenoxybenzoyl)benzene, 12.18g (0.06mol) of terephthaloyl chloride and 1170g of o-dichlorobenzene were added. Stirring was started and the temperature was lowered to -10℃. 70g of aluminum chloride was added to the reactor. After the addition was completed, the mixture was stirred for 10min. The temperature was then raised to 25℃ and reacted for 30min. The temperature was then lowered to -5℃. 8.12g (0.04mol) of isophthaloyl chloride, 0.6g (0.004mol) of benzoyl chloride and 18g of aluminum chloride were added. After the addition was completed, the mixture was stirred for 10min and the temperature was raised to 90℃. The reaction time was recorded as 30min. After the temperature was lowered to 30℃, the material was removed to obtain the reaction product.

[0081] (2) The reaction product obtained in step (1) is transferred to the decomplexing vessel, and a 3% hydrochloric acid aqueous solution is slowly added to it. The temperature in the decomplexing vessel is controlled to not exceed 60°C. The mixture is stirred for 2 hours and then cooled to 30°C. The polymer and liquid are separated by centrifugation. The wet polymer is then washed sequentially with hydrochloric acid solution, methanol and sodium hydroxide solution and water. It is then dried under vacuum at 190°C for 12 hours to obtain the highly crystalline polyether ketone ketone.

[0082] Example 2

[0083] A method for preparing highly crystalline polyether ketone includes the following steps:

[0084] (1) Nitrogen gas was introduced into a dry 2L reactor. 48g (0.1mol) of 1,4-bis(phenoxybenzoyl)benzene, 12.18g (0.06mol) of terephthaloyl chloride and 1170g of o-dichlorobenzene were added. Stirring was started and the temperature was lowered to -5℃. 70g of aluminum chloride was added to the reactor. After the addition was completed, the mixture was stirred for 10min. The temperature was then raised to 50℃ and reacted for 30min. At this temperature, 8.12g (0.04mol) of isophthaloyl chloride, 0.6g (0.004mol) of benzoyl chloride and 18g of aluminum chloride were added. After the addition was completed, the mixture was stirred for 10min and the temperature was raised to 90℃. The reaction time was recorded as 30min. After the temperature was lowered to 30℃, the material was removed to obtain the reaction product.

[0085] (2) The reaction product obtained in step (1) is transferred to the decomplexing vessel, and a 3% hydrochloric acid aqueous solution is slowly added to it. The temperature in the decomplexing vessel is controlled to not exceed 60°C. The mixture is stirred for 2 hours and then cooled to 30°C. The polymer and liquid are separated by centrifugation. The wet polymer is then washed sequentially with hydrochloric acid solution, methanol and sodium hydroxide solution and water. It is then dried under vacuum at 190°C for 12 hours to obtain the highly crystalline polyether ketone ketone.

[0086] Example 3

[0087] A method for preparing highly crystalline polyether ketone includes the following steps:

[0088] (1) Nitrogen gas was introduced into a dry 2L reactor. 48g (0.1mol) of 1,4-bis(phenoxybenzoyl)benzene, 12.18g (0.06mol) of terephthaloyl chloride and 1170g of o-dichlorobenzene were added. Stirring was started and the temperature was lowered to -5℃. 70g of aluminum chloride was added to the reactor. After the addition was completed, the mixture was stirred for 10min. The temperature was then raised to 35℃ and reacted for 30min. The temperature was then lowered to -5℃. 8.12g (0.04mol) of isophthaloyl chloride, (0.6g (0.004mol) of benzoyl chloride) and 18g of aluminum chloride were added. After the addition was completed, the mixture was stirred for 10min and the temperature was raised to 100℃. The reaction time was recorded as 30min. After the temperature was lowered to 30℃, the material was removed to obtain the reaction product.

[0089] (2) The reaction product obtained in step (1) is transferred to the decomplexing vessel, and a 3% hydrochloric acid aqueous solution is slowly added to it. The temperature in the decomplexing vessel is controlled to not exceed 60°C. The mixture is stirred for 2 hours and then cooled to 30°C. The polymer and liquid are separated by centrifugation. The wet polymer is then washed sequentially with hydrochloric acid solution, methanol and sodium hydroxide solution and water. It is then dried under vacuum at 190°C for 12 hours to obtain the highly crystalline polyether ketone ketone.

[0090] Example 4

[0091] A method for preparing highly crystalline polyether ketone includes the following steps:

[0092] (1) Nitrogen gas was introduced into a dry 2L reactor. 48g (0.1mol) of 1,4-bis(phenoxybenzoyl)benzene, 8.12g (0.04mol) isophthaloyl chloride and 1170g o-dichlorobenzene were added. Stirring was started and the temperature was lowered to -10℃. 70g of aluminum chloride was added to the reactor. After the addition was completed, the mixture was stirred for 10min. The temperature was then raised to 25℃ and reacted for 30min. At this temperature, 12.18g (0.06mol) terephthaloyl chloride, 0.6g (0.004mol) benzoyl chloride and 18g of aluminum chloride were added. After the addition was completed, the mixture was stirred for 10min and the temperature was raised to 90℃. The reaction time was recorded as 30min. After the temperature was lowered to 30℃, the material was removed to obtain the reaction product.

[0093] (2) The reaction product obtained in step (1) is transferred to the decomplexing vessel, and a 3% hydrochloric acid aqueous solution is slowly added to it. The temperature in the decomplexing vessel is controlled to not exceed 60°C. The mixture is stirred for 2 hours and then cooled to 30°C. The polymer and liquid are separated by centrifugation. The wet polymer is then washed sequentially with hydrochloric acid solution, methanol and sodium hydroxide solution and water. It is then dried under vacuum at 190°C for 12 hours to obtain the highly crystalline polyether ketone ketone.

[0094] Example 5

[0095] A method for preparing highly crystalline polyether ketone is disclosed, which differs from Example 1 in that 0.1 mol of diphenyl ether is used instead of 0.1 mol of 1,4-bis(phenoxybenzoyl)benzene, while the other substances, amounts, and preparation methods are the same as in Example 1.

[0096] Comparative Example 1

[0097] A method for preparing polyether ketone includes the following steps:

[0098] (1) Nitrogen gas was introduced into a dry 2L reactor. 47g (0.1mol) of 1,4-bis(phenoxybenzoyl)benzene, 12.18g (0.06mol) terephthaloyl chloride, 8.12g (0.04mol) isophthaloyl chloride, 0.6g (0.004mol) benzoyl chloride and 1170g o-dichlorobenzene were added. Stirring was started and the temperature was set to -10℃. 85g of aluminum chloride was added to the reactor. After the addition was completed, the mixture was stirred for 10min. Then the temperature was raised to 90℃. The reaction time was recorded as 30min. After cooling to 30℃, the material was removed.

[0099] (2) The reaction product obtained in step (1) is transferred to the decomplexing vessel, and a 3% hydrochloric acid aqueous solution is slowly added to it. The temperature in the decomplexing vessel is controlled to not exceed 60°C. The mixture is stirred for 2 hours and then cooled to 30°C. The polymer and liquid are separated by centrifugation. The wet polymer is then washed sequentially with hydrochloric acid solution, methanol and sodium hydroxide solution and water. It is then dried under vacuum at 190°C for 12 hours to obtain the polyether ketone ketone.

[0100] Performance testing:

[0101] (1) Nuclear Magnetic Resonance (NMR) Test: The highly crystalline polyether ketone ketone prepared in Example 1 was tested using a nuclear magnetic resonance (NMR) spectrometer. The test solvent was trifluoroacetic acid-CDCl3, and the frequency was 400 MHz. The 1H NMR spectrum of the highly crystalline polyether ketone ketone prepared in Example 1 is shown below. Figure 1 As shown;

[0102] from Figure 1 It can be seen that the polyether ketone prepared by the preparation method provided in Example 1 has a highly linear structure, that is, it contains very few or no ortho-branched structures.

[0103] (2) DSC test: The highly crystalline polyether ketone ketone prepared in Example 1 was tested using a differential scanning calorimeter (DSC). The first heating cycle involved heating from 30°C to 400°C at a rate of 10°C / min, followed by isothermal treatment at 400°C for 1 min. The first cooling cycle involved cooling from 400°C to 30°C at a rate of 10°C / min, followed by isothermal treatment for 1 min. The second heating cycle involved heating from 30°C to 400°C at a rate of 10°C / min, followed by isothermal treatment at 400°C for 1 min. The DSC curve of the highly crystalline polyether ketone ketone prepared in Example 1 is shown below. Figure 2 As shown, Figure 2 In, the enthalpy of fusion (ΔH) m The integral of the melting endothermic curve during the second heating cycle scan was determined to be the melting temperature (T). m The peak temperature of the melting endothermic curve during the second heating cycle scan was determined to be the enthalpy of crystallization (ΔH). c The integral of the endothermic curve of crystallization during the first cooling cycle scan was determined, and the crystallization temperature (Tc) was determined as the peak temperature of the exothermic curve of crystallization during the first cooling cycle scan.

[0104] from Figure 2 It can be seen that the highly crystalline polyether ketone ketone prepared by the preparation method provided in Example 1 has a high melting enthalpy, up to 43.4 J / g.

[0105] (3) Thermal stability: Temperature at which 2% weight loss occurs (Td) 2%The symbol indicates thermal stability, measured using a thermogravimetric analyzer (TGA) according to the test method provided by ASTM D3850. The TGA used is NETZSCH 209F1. The highly crystalline polyether ketone ketone prepared in Example 1 was tested under nitrogen atmosphere (60 mL / min) at a rate of 10 °C / min from 30 °C to 700 °C. The TGA thermogravimetric analysis (TGA) curve of the highly crystalline polyether ketone ketone prepared in Example 1 is shown in the figure below. Figure 3 As shown;

[0106] from Figure 3 It can be seen that the highly crystalline polyether ketone ketone prepared by the method provided in Example 1 has high thermal stability, Td 2% Greater than 500℃.

[0107] (4) Crystallinity: Crystallinity is calculated using the following formula;

[0108]

[0109] Where: ΔH m The enthalpy of fusion (J / g), ΔH cc The enthalpy of cold crystallization (J / g), ΔH 100% The enthalpy of complete crystallization of the polymer is taken as the same as that of PEEK, which is 130 J / g.

[0110] (5) Half-crystallization time: The half-crystallization time of the material was measured using a DSC analyzer under isothermal conditions;

[0111] The specific testing method includes: first, stabilizing the temperature at 30℃, then gradually increasing the temperature to 380℃ at a heating rate of 20℃ / min, holding it for 5 minutes, and finally cooling the temperature from 380℃ to 310℃ at a cooling rate of 40℃ / min, holding it at 310℃ for 60 minutes, and then cooling it to 30℃. The crystallization time at 310℃ is recorded as the time required for the material to reach half of its maximum crystallinity content, which is the semi-crystallization time.

[0112] The polyetherketones provided in Examples 1 to 5 and Comparative Example 1 were tested according to the test methods (2) to (5) provided above, and the test data are recorded in Table 1;

[0113] Table 1

[0114] <![CDATA[ΔH m (J / g)]]> Crystallinity (%) Semi-crystallization time (min) <![CDATA[Td 2% (℃)]]> Example 1 43 33.8 1.1 547.5 Example 2 47 36.1 1.0 539.2 Example 3 43 33.1 1.1 534.9 Example 4 44 33.8 1.1 538.4 Example 5 30 23 3 441 Comparative Example 1 27 20.7 2.5 501.2

[0115] According to the data in Table 1:

[0116] (1) The ΔH of the polyether ketones prepared by the preparation methods provided in Examples 1-4 mIt has a high crystallinity of 43–47 J / g, a crystallinity of 33.1–36.1%, and a semi-crystallization time of only 1.0–1.1 min. 2% The temperatures ranged from 534.9 to 547.5°C, indicating that the polyether ketones prepared by the methods provided in Examples 1 to 4 have higher melting enthalpy, higher crystallinity, shorter half-crystallization time, faster crystallization rate, and higher thermal stability.

[0117] (2) Compared with Example 1, the preparation method provided in Example 5 uses diphenyl ether to replace 1,4-bis(phenoxybenzoyl)benzene as an aromatic monomer containing two active hydrogens. The method steps are the same as in Example 1. However, the melting enthalpy and crystallinity of the polyether ketone prepared are reduced. This indicates that the chain regularity of the polyether ketone prepared by diphenyl ether is low and there may be branching, which reduces the crystallinity.

[0118] (3) Compared with Example 1, Comparative Example 1 uses random copolymerization, which can improve the regularity of polyetherketone chains to a certain extent. However, because the polyetherketone synthesized by random copolymerization is short-range ordered but long-range disordered, the crystallization performance is still weak, with a crystallinity of only 20.7% and a crystallization time as high as 2.4 min. This also shows that crystallization depends on polymer chains with linear and regular structures. These polymer chains can be stacked in an orderly manner to form crystals. Therefore, any behavior that changes the polyetherketone skeleton structure by branching will hinder its crystallization process.

[0119] The applicant declares that this invention illustrates a highly crystalline polyether ketone ketone, its preparation method, and its applications through the above embodiments. However, this invention is not limited to the above process steps, meaning that this invention does not necessarily rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of the raw materials used in this invention, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection and disclosure scope of this invention.

Claims

1. A method for preparing highly crystalline polyether ketone, characterized in that, The preparation method includes the following steps: (1) Mix an aromatic monomer containing two active hydrogens, an aromatic monomer containing two active acyl chlorides and a solvent, cool down for the first time, then add a first acid catalyst, heat up for the first time and carry out the first reaction, then add the isomer of the aromatic monomer containing two active acyl chlorides, a second acid catalyst and a capping agent, heat up for the second time and carry out the second reaction to obtain the reaction product. (2) The reaction product obtained in step (1) is subjected to decomplexation and post-treatment to obtain the highly crystalline polyether ketone ketone.

2. The preparation method according to claim 1, characterized in that, The aromatic monomer containing two active hydrogens in step (1) includes any one or a combination of at least two of bis(phenoxybenzoyl) ketone, 1,4-bis(4-phenoxybenzoyl)benzene or 1,3-bis(4-phenoxybenzoyl)benzene, preferably 1,4-bis(4-phenoxybenzoyl)benzene and / or 1,3-bis(4-phenoxybenzoyl)benzene; Preferably, the aromatic monomer containing two active acyl chlorides in step (1) is an aromatic monomer with a para structure, and the isomer of the aromatic monomer containing two active acyl chlorides is an aromatic monomer with a meta structure. Preferably, the aromatic monomer containing two active acyl chlorides in step (1) is an aromatic monomer with a meta structure, and the isomer of the aromatic monomer containing two active acyl chlorides is an aromatic monomer with a para structure; Preferably, the aromatic monomer having a para structure includes any one or a combination of at least two of the following compounds B1 to B5; Preferably, the aromatic monomer having a para-position structure is terephthaloyl chloride; Preferably, the aromatic monomer having a meta structure is a meta isomer of compounds B1 to B5; Preferably, the aromatic monomer having a meta-structure is isophthaloyl chloride; Preferably, the capping agent in step (1) includes any one or a combination of at least two of benzoyl chloride, 4-phenoxybenzophenone, benzenesulfonyl chloride, 4-biphenyl, bis(4-oxyphenyl) ketone or biphenyl.

3. The preparation method according to claim 1 or 2, characterized in that, Based on the total molar amount of the aromatic monomer containing two active hydrogens, the aromatic monomer containing two active acyl chlorides and its isomers and the capping agent described in step (1) being 100%, the molar content of the aromatic monomer containing two active hydrogens described in step (1) is 48-51%. Preferably, based on the total molar amount of the aromatic monomer containing two active hydrogens, the aromatic monomer containing two active acyl chlorides and its isomers and the capping agent in step (1) being 100%, the molar content of the aromatic monomer containing two active acyl chlorides in step (1) is 25-50%. Preferably, based on the total molar amount of the aromatic monomer containing two active hydrogens, the aromatic monomer containing two active acyl chlorides and its isomers and the capping agent in step (1) being 100%, the molar content of the isomer of the aromatic monomer containing two active acyl chlorides in step (1) is 5-25%. Preferably, the molar content of the capping agent in step (1) is 1 to 11%, based on the total molar amount of the aromatic monomer containing two active hydrogens, the aromatic monomer containing two active acyl chlorides and their isomers and the capping agent in step (1) being 100%.

4. The preparation method according to any one of claims 1 to 3, characterized in that, Step (1) Both the first acid catalyst and the second acid catalyst are Lewis acid catalysts; Preferably, with the total molar amount of carbonyl groups in the system of step (1) being 100%, the total molar amount of the first acid catalyst and the second acid catalyst in step (1) is 100-300%, more preferably 110-250%, even more preferably 120-220%, even more preferably 130-200%, and even more preferably 140-180%.

5. The preparation method according to any one of claims 1 to 4, characterized in that, The solvent in step (1) includes any one of dichloromethane, 1,2-dichloroethane, o-dichlorobenzene, tetrachloroethylene, 1,2,4-trichlorobenzene, o-difluorobenzene, nitromethane, nitrobenzene, 1,3-dichlorobenzene or 1,1,2,2-tetrachloroethane, preferably o-dichlorobenzene and / or dichloromethane, and more preferably o-dichlorobenzene; Preferably, the molar concentration of the aromatic monomer containing two active hydrogens in the system of step (1) is 0.05 to 0.5 mol / L.

6. The preparation method according to any one of claims 1 to 5, characterized in that, The temperature of the system after the first cooling in step (1) is -30 to -5℃; Preferably, the temperature of the system after the first heating in step (1) is 0–150°C; Preferably, the time for the first reaction in step (1) is 0.1 to 12 hours; Preferably, step (1) further includes a second cooling step before adding the isomer of the aromatic monomer containing two active acyl chlorides, the second acid catalyst, and the capping agent; Preferably, the temperature of the system after the second cooling is -30 to 50°C; Preferably, the temperature of the system after the second heating in step (1) is 50–150°C; Preferably, the second reaction in step (1) takes 0.1 to 12 hours.

7. The preparation method according to any one of claims 1 to 6, characterized in that, The method for decomplexing in step (2) specifically includes: transferring the reaction product obtained in step (1) to the decomplexing vessel and adding a proton solution for decomplexing; Preferably, the amount of proton solution added is greater than the total amount of the first acid catalyst and the second acid catalyst in step (1); Preferably, the post-processing in step (2) includes centrifugation, washing and drying.

8. A highly crystalline polyether ketone, characterized in that, The highly crystalline polyether ketone ketone is prepared by the preparation method according to any one of claims 1 to 7; Preferably, the highly crystalline polyether ketone ketone has the morphology of a porous, irregular fine-grained solid, spherical particles, or powder; Preferably, the intrinsic viscosity of the highly crystalline polyether ketone is 0.5–2.5 dL / g; Preferably, the high crystallinity polyether ketone has a crystallinity ≥ 3.8%; Preferably, the melting enthalpy of the highly crystalline polyether ether ketone is >5 J / g, more preferably ≥20 J / g, even more preferably ≥30 J / g, and still more preferably ≥41 J / g.

9. The application of the highly crystalline polyether ketone as described in claim 8 in the preparation of composite materials.

10. A polyether ketone ketone composite material, characterized in that, The polyether ketone ketone composite material includes reinforcing fibers and the highly crystalline polyether ketone ketone as described in claim 8; Preferably, the reinforcing fiber includes any one or a combination of at least two of carbon fiber, glass fiber, aramid fiber, silicon carbide fiber, polyester fiber, ceramic fiber, alumina fiber, boron fiber, metal fiber, mineral fiber, rock fiber or slag fiber, more preferably any one or a combination of at least two of carbon fiber, glass fiber or aramid fiber, and more preferably carbon fiber. Preferably, the polyether ketone ketone composite material also contains fillers and / or additives; Preferably, the filler comprises any one or a combination of at least two of talc, mica, kaolin, calcium carbonate, calcium silicate, or boron nitride; Preferably, the additives include any one or a combination of at least two of antioxidants, light stabilizers, flame retardants, plasticizers, inorganic fillers, or internal mold release agents.

Citation Information

Patent Citations

  • Preparation method of block polyether ketone ketone

    CN107973902A

  • High crystallinity polyether ketone ketone and preparation method thereof

    CN109593183A